Dissection of hubs and bottlenecks in a protein-protein interaction network. (February 2023) - Nithya, Chandramohan; Kiran, Manjari; Nagarajaram, Hampapathalu Adimurthy
Abstract: Analysis of degree centrality in conjunction with betweenness centrality of proteins in a human protein-protein interaction network revealed three categories of centrally important proteins: a) proteins with high degree and betweenness (hub-bottlenecks denoted as MX), b) proteins with high betweenness and low degree (non-hub-bottlenecks/pure bottlenecks denoted as PB) and c) proteins with high degree and low betweenness (hub-non-bottlenecks/pure hubs denoted as PH). When subjected to a detailed statistical analysis of their molecular-level properties, the proteins belonging to each of these categories were found to be associated with distinct canonical molecular properties, i.e., "molecular markers". The MX proteins are a) conformationally versatile, mainly comprising of essential proteins, b) the targets for interactions by the proteins of viral and bacterial pathogens, c) evolutionally constrained, involved in multiple pathways, enriched with disease genes and d) involved in the functions such as protein stabilization, phosphorylation, and mRNA slicing processes. PB proteins are a) enriched with extracellular and cancer-related proteins, b) enriched with the approved drug targets and c) involved in cell-cell signaling processes. Finally, PH are a) structurally versatile, b) enriched with essential proteins primarily involved in housekeeping processes (transcription and replication). The fact that the proteins belonging to these three categories form three distinct sets in terms of their molecular properties reveals the existence of trichotomy among hubs and bottlenecks, and this knowledge is of paramount importance while prioritizing protein targets for further studies such as drug design and disease association studies based on their network centrality values. Graphical Abstract: ga1 Highlights: Studies in literature have identified three categories of proteins, viz., hub-bottlenecks, non-hub-bottlenecks and hub-non-bottlenecks, based on their differential centrality values and have so far emphasised their evolutionary conservation. However, till today no comprehensive statistics-based analysis has ever been reported on their molecular properties to show that the proteins belonging to these network-based categories have distinct molecular properties and hence form three different sets of proteins. We conducted a detailed analysis described in the manuscript, such as proteins' structure flexibility, functions, turn-over rates and disease association. In addition, we used a human protein-protein interaction network almost double the size of the interactome used in the previous studies. Our study not only reveals that the proteins belonging to the three categories have distinct molecular properties and hence form distinct sets but also demonstrates that the topological roles of proteins in the human protein-protein interaction network are correlated to their molecular properties. This study is of significance and importance because this not only confirms the existence of trichotomy among the proteins with high degree and high betweenness values but also demonstrates that the proteins belonging to each of these categories are associated with distinct molecular features and hence are with unique "molecular markers". The "molecular markers" in conjunction with network properties of proteins are helpful when prioritising proteins for further studies such as drug design and disease association.